Design and Construction of Screw Type Micro Hydro Power Plant - Sagita Rochman; Andy Hermawan (BEST, 2022)
The development of renewable energy is growing rapidly along with technological developments. One application of renewable energy is hydroelectric power (Water Turbine Generator). This study aims to design and manufacture a MHP using a permanent magnet generator with a screw type turbine and determine the output power generated from a MHP generator using a screw type turbine. In this research, an efficient and efficient MHP with screw type turbine will be developed. This research will be implemented in Doplang Tretek, Prambon Subdistrict, Sidoarjo Regency. MHP is a power plant whose driving force comes from water flowing from the highlands to the lowlands. By utilizing the water discharge PLTMH can function to produce electricity which is driven through a turbine and rotates a generator. The main components of MHP are turbine, generator, and water discharge. If one of these components is not present, the MHP cannot function. By utilizing MHP we can enjoy electricity for free, the power generated by MHP is still small <0.5-100kW. From the design of the PLTMH generator using a screw type turbine the output voltage is 9 volts with a water flow of 557 m3/s. The greater the flow of water flowing in the cross section of the turbine, the faster the resulting rpm.